Beach read - Henry, Emily (Jove, 2020)
"A romance writer who no longer believes in love and a literary writer stuck in a rut engage in a summer-long challenge that may just upend everything they believe about happily ever afters. Augustus Everett is an acclaimed author of literary fiction. January Andrews writes bestselling romance. When she pens a happily ever after, he kills off his entire cast. They're polar opposites. In fact, the only thing they have in common is that for the next three months, they're living in neighboring beach houses, broke, and bogged down with writer's block. Until, one hazy evening, one thing leads to another and they strike a deal designed to force them out of their creative ruts: Augustus will spend the summer writing something happy, and January will pen the next Great American Novel. She'll take him on field trips worthy of any rom-com montage, and he'll take her to interview surviving members of a backwoods death cult (obviously). Everyone will finish a book and no one will fall in love. But as the summer stretches on, January discovers a gaping plot hole in the story she's been telling herself about her own life, and begins to wonder what other things she might have gotten wrong, including her ideas about the man next door."--Provided by publisher.